Challenges Of Standard Inpatient Class Policy In Indonesia: : Scoping Review - Sophie Aileen; Cahya Tri Purnami; Sutopo Patria Jati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The standard inpatient class policy in Indonesia has been stated in legislation since 2021 with twelve criteria and must be fully met by December 2024. This study aims to get an overview of the readiness of hospitals in Indonesia to meet the policy and an overview of the community's perspective in responding to standard inpatient classes. Scoping Review with Arksey and O'Malley and Beyond's approach. Online article search on Scopus, Science Direct, SpringerLink, garuda, and Google Scholar, published in 2020-2023, articles published in English and Indonesian, with search keywords: 'kris' or 'jk' or 'bpjs and kesehatan' or 'bpjs and health' or 'inpatient and room' or 'health and policy and jkn', in October 2023 and carried out Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram. Hospitals in Indonesia studied in 2022 are not ready, but hospital research in 2023 states that they are ready to carry out Standard Inpatient Classes (KRIS). The community as patients and consumers in the use of health services from the Social Security Organizing Agency (BPJS) Health provides support in the implementation of Standard Inpatient Classes. Meanwhile, from the legality aspect, there is a discrepancy in regulations from the highest to its derivatives, there is even no clarity on legal sanctions if the Hospital does not meet the criteria for the Standard Inpatient Class according to the specified time limit